In vitro evaluation of poloxamer in situ forming gels for bedaquiline fumarate salt and pharmacokinetics following intramuscular injection in rats - Sandy Van Hemelryck; Jonatan Dewulf; Harm Niekus; Marjolein van Heerden; Benno Ingelse; René Holm; Erik Mannaert; Peter Langguth (Elsevier, 2019)
The objective of this study was to evaluate in vitro and in vivo drug release from in situ forming gels prepared with poloxamer 338 (P338) and/or 407 (P407) in N-methyl-2-pyrrolidone (NMP)/water mixtures for the model compound bedaquiline fumarate salt. The impact of total poloxamer concentration (20%-25% (w/w)), P338/P407 ratio (100/0%-0/100% (w/w)) and NMP/water ratio (0/100%-25/75% (v/v)) on gel point temperature (GPT) was investigated via a design of experiments (DoE), showing that GPT decreased mainly with increasing poloxamer concentration and decreasing P338/P407 ratio, while the relation with NMP/water ratio was more complex resulting in a flexion. Based on the DoE, four formulations with 10 mg/g bedaquiline fumarate salt, a fixed NMP/water ratio of 25/75% (v/v) and varying total poloxamer concentration and P338/P407 ratio were selected for evaluation of gel erosion in vitro. The fastest eroding formulation had the lowest total poloxamer concentration (20% (w/w)) and the lowest P338/P407 ratio (20.4/79.6% (w/w)), while the formulation with the highest total poloxamer concentration (23.5% (w/w)) and highest P338/P407 ratio (100/0% (w/w)) showed the lowest gel erosion rate. These fast and slow eroding formulations showed a similar trend for in vitro drug release and in vivo pharmacokinetics after intramuscular (IM) injection in rats. In vivo tmax of the IM administered poloxamer in situ forming gels was about 6 h and a short-term sustained drug release was observed in vivo in rats up to 24 h after dosing, similar to a solution of bedaquiline fumarate salt in polyethylene glycol (PEG400)/water. In conclusion, IM administration of the evaluated poloxamer in situ forming gels may be useful for drugs that require a short-term sustained release, but is not able to extend drug release rates up to weeks or months. Keywords: In situ forming gels, Poloxamer, Gel erosion, In vitro release, Pharmacokinetics, Sustained release